2022
DOI: 10.3389/fimmu.2022.897413
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Xanthine Oxidase as a Potential Biomarker in Stroke Diagnostics

Abstract: Stroke is one of the most common cerebrovascular diseases. Despite significant progress in understanding stroke pathogenesis, cases are still increasing. Thus, laboratory biomarkers of stroke are sought to allow rapid and non-invasive diagnostics. Ischemia-reperfusion injury is an inflammatory process with characteristic cellular changes leading to microvascular disruption. Several studies have shown that hyperactivation of xanthine oxidase (XO) is a major pathogenic factor contributing to brain dysfunction. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 89 publications
(113 reference statements)
0
11
0
Order By: Relevance
“…They also had not taken any medications at least 8 hours before saliva collection. After rinsing the mouth twice with room-temperature distilled water, patients spat out saliva accumulated at the bottom of the mouth, for 15 minutes, into a sterile centrifuge tube placed in a container with ice ( 23 ). The volume of saliva was measured with a single-channel pipette with accuracy of 100 μL and was the basis for calculating the salivary flow rate (SFR; mL/min).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also had not taken any medications at least 8 hours before saliva collection. After rinsing the mouth twice with room-temperature distilled water, patients spat out saliva accumulated at the bottom of the mouth, for 15 minutes, into a sterile centrifuge tube placed in a container with ice ( 23 ). The volume of saliva was measured with a single-channel pipette with accuracy of 100 μL and was the basis for calculating the salivary flow rate (SFR; mL/min).…”
Section: Methodsmentioning
confidence: 99%
“…Instruments, Warsaw, Poland), and plasma was collected for assays. The antioxidant butylated hydroxytoluene (BHT) was added to the samples ( 23 ). Samples were stored at -80°C for no longer than six months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A basic study reported that in a rat model of AIS, XO expression on the infarcted side was significantly higher than that on the noninfarcted side and continued to increase over time [ 18 ]. A recent study conducted by Mateusz M et al indicated that salivary XO may be a potential biomarker for the diagnosis of stroke, which provides a new simple strategy for early prediction in patients with AIS [ 19 ]. However, few studies have confirmed the clinical value of serum XO levels in the pathogenesis of AIS [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Saliva samples are utilized in various diagnostic assays, including COVID-19 [1][2][3][4]. During the COVID-19 pandemic, large biobanks were started to provide clinical samples for several different studies, including pivotal validation assays needed to obtain regulatory clearance for new diagnostic tests.…”
Section: Introductionmentioning
confidence: 99%